Diagnostic Pitfall of Platypnea-Orthodeoxia Syndrome Caused by Atrial Septal Defect after Right Pneumonectomy. (21st February 2020) - Bohren, Y.; Lopez, M.; Santelmo, N.; Ristorto, J.; Billaud, P.; Canuet, M.; Mertes, P. M.; Collange, O.
Abstract : We describe a case of platypnea-orthodeoxia syndrome (POS) due to atrial septal defect (ASD) occurring in the early postoperative course of a right pneumonectomy. Deformation of the atrial septum after right pneumonectomy deviates the blood from the inferior vena cava to ASD during the sitting position creating, a massive right-to-left shunt. Diagnosis can initially be missed by making contrast bubble test through the superior vena cava. The atrial septal defect was then closed using the surgical technique, allowing an instantaneous improvement of hematosis.